A Review of Business Model Transformation in Transportation Business Post Pandemic - Nia Kurniati Bachtiar; M. Elfan Kaukab (Automotive Experiences, 2022)
This study reviews post-pandemic business models, as demonstrated in transportation business by employing literature study method. Data obtained includes 56 articles published from 2020 to 2022 during Covid-19 pandemic that transform the business model. The results of the study indicate that there are six streams in the literature, namely (1) the impact of Covid-19 on the transportation sector, (2) the built environment for business model transportation, (3) the need for transformation of business models due to new policies, (4) changes in consumer choices and behavior, (5) supply chain management and transportation transformation, and (6) transportation business model planning. The synthesis resulted in a transportation sustainable business model transformation framework involving threat identification, company character, support, built environment, resources and capabilities, design and development, and delivery and evaluation. The transportation business needs to identify aspects of transportation services that need to be improved, adjust internal resources and capabilities, reconfigure the business, and encourage collective agreements to transform the post-pandemic transportation business model. This research contributes to the literature on transform the regular business model. It emphasizes the importance of resources and capabilities to drive business transformation internally and externally in the context of the transportation business.